Criminal law - Scheb, John M. (John Malcolm) 1926-; Scheb, John M. II 1955- (2012)
Written in simple, understandable terms, this title combines traditional presentation of case law with coverage of trends as it describes both the reasoning behind criminal law and the practical applications of that law